2009
DOI: 10.1111/j.1365-2222.2009.03362.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effects of sulphite additives

Abstract: Sulphites are widely used as preservative and antioxidant additives in the food and pharmaceutical industries. Topical, oral or parenteral exposure to sulphites has been reported to induce a range of adverse clinical effects in sensitive individuals, ranging from dermatitis, urticaria, flushing, hypotension, abdominal pain and diarrhoea to life-threatening anaphylactic and asthmatic reactions. Exposure to the sulphites arises mainly from the consumption of foods and drinks that contain these additives; however… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
229
1
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 414 publications
(265 citation statements)
references
References 75 publications
5
229
1
8
Order By: Relevance
“…The SO 2 acts as microbiological control agent in musts and wines and as enzyme inhibitor to prevent must browning and wine oxidation [6,7]. Although this addition is considered to be almost inevitable in the production of wine, it is also known that an excess SO 2 intake can cause health problems in sensitive people, particularly headaches, allergies, gastric irritation, nausea, and difficulties in breathing in asthma patients [8][9][10]. In this point of view, the International Organization of Vine and Wine (OIV) has been progressively reducing the maximum concentration authorized in wines, which is 150 mg/l for red wines and 200 mg/l for white wines nowadays (Regulation (EC) No 606/2009).…”
Section: Introductionmentioning
confidence: 99%
“…The SO 2 acts as microbiological control agent in musts and wines and as enzyme inhibitor to prevent must browning and wine oxidation [6,7]. Although this addition is considered to be almost inevitable in the production of wine, it is also known that an excess SO 2 intake can cause health problems in sensitive people, particularly headaches, allergies, gastric irritation, nausea, and difficulties in breathing in asthma patients [8][9][10]. In this point of view, the International Organization of Vine and Wine (OIV) has been progressively reducing the maximum concentration authorized in wines, which is 150 mg/l for red wines and 200 mg/l for white wines nowadays (Regulation (EC) No 606/2009).…”
Section: Introductionmentioning
confidence: 99%
“…Takvi spojevi su, primjerice, natrijev i kalijev hidrogensulfit, natrijev i kalijev disulfit te natrijev sulfit, koji se upotrebljavaju kao konzervansi jer sprječavaju neenzimsko tamnjenje hrane (Maillardove reakcije), enzimske reakcije i djelovanje mikroba. [128][129][130][131] Maksimalne dozvoljene količine sulfita propisane su za svaku vrstu hrane i pića. 128 Sulfiti se unose i dodatcima prehrani, lijekovima i kozmetičkim sredstvima.…”
unclassified
“…However, several studies have reported that high exposures to this additive can produce organoleptic alterations in the final product and can cause health adverse effects in sensitive people [1]. Because of this, the sulfating practice is actually strictly controlled in musts and wines.…”
Section: Introductionmentioning
confidence: 99%